A Pilot Intervention Designed to Address Behavioral Factors That Place Overweight/Obese Young Children at Risk for Later-Life Obesity. (August 2017) - Small, Leigh; Thacker, Leroy; Aldrich, Heather; Bonds-McClain, Darya; Melnyk, Bernadette
The purpose of this pilot randomized controlled trial (RCT) was to intervene with parents of overweight/obese 4- to 8-year-old children to improve child internalizing and externalizing behaviors. Parent–child dyads ( N = 60) were randomly assigned to treatment or comparison conditions. Parents attended four intervention sessions at their child's primary health care office over 3 months. Child behaviors were assessed at 0, 3, 6, and 12 months post intervention. Parental beliefs in their skills/abilities increased in the experimental group parents, but there was no statistical difference between groups at any time. Child externalizing behaviors significantly decreased from baseline to postintervention for both groups ( F = 3.26, p = .020). Post hoc model testing suggests that this change was more pronounced in the intervention group ( F = 0.56, p = .692). Child somatic symptoms significantly decreased over time ( F = 4.55, p = .004), and there were group differences in child depressive behaviors ( F = 6.19, p = .020). These findings suggest that a parent-focused intervention program demonstrated positive preliminary effects on children's behaviors.